2015
DOI: 10.1038/nature15252
|View full text |Cite
|
Sign up to set email alerts
|

Tet2 is required to resolve inflammation by recruiting Hdac2 to specifically repress IL-6

Abstract: Epigenetic modifiers have fundamental roles in defining unique cellular identity through the establishment and maintenance of lineage-specific chromatin and methylation status1. Several DNA modifications such as 5-hydroxymethylcytosine (5hmC) are catalysed by the ten eleven translocation (Tet) methylcytosine dioxygenase family members2, and the roles of Tet proteins in regulating chromatin architecture and gene transcription independently of DNA methylation have been gradually uncovered3. However, the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
559
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 662 publications
(630 citation statements)
references
References 29 publications
42
559
4
Order By: Relevance
“…The histone deacetylase HDAC11 has been found to inhibit IL-10 expression (41), whereas phosphorylation of histone H3 at serine 10 is needed for transcriptional activation of the Il10 promoter (42). A recent study found that IB recruits the epigenetic modifier Tet2 to selective promoter regions independent of DNA meth- ylation (43). IB further mediates chromatin remodeling by recruiting the SWI/SNF complex to target genes, thereby enhancing promoter accessibility (32).…”
Section: Discussionmentioning
confidence: 99%
“…The histone deacetylase HDAC11 has been found to inhibit IL-10 expression (41), whereas phosphorylation of histone H3 at serine 10 is needed for transcriptional activation of the Il10 promoter (42). A recent study found that IB recruits the epigenetic modifier Tet2 to selective promoter regions independent of DNA meth- ylation (43). IB further mediates chromatin remodeling by recruiting the SWI/SNF complex to target genes, thereby enhancing promoter accessibility (32).…”
Section: Discussionmentioning
confidence: 99%
“…51 During the late phase of inflammatory response, induction of de novo 5-hydroxymethylation upstream of the Il6 locus by a methylcytosine dioxygenase TET2 recruits HDAC2 to inhibit Il6 transcription via histone deacetylation and is critical for termination of the high transcription of Il6. 52 It will be intriguing to further investigate the molecular mechanisms and physiological relevance of epigenetic modification at different phases of innate inflammatory response.…”
Section: Molecular Regulation Of Innate Immunity and Inflammationmentioning
confidence: 99%
“…TET1 and TET2 act predominantly as tumor suppressors. Re-introduction and overexpression of these proteins is able to restore the 5hmC content, and to suppress invasion and growth in certain tumors (37)(38)(39)(40)(41). A previous report revealed that a deficiency in SOCS3 may promote tumor development, since it has tumor suppressor functions in numerous cancer cell types (29).…”
Section: Discussionmentioning
confidence: 99%